Impact of Currency Risk on the Performance of Microfinance Institutions in Emerging Economies - Manchkhashvili, Nino (2024)
Microfinance Institutions play an important role in providing financial services to the underserved population. However, operating in volatile economic environments, such as emerging markets, exposes them to foreign exchange risk. This dissertation explores the drivers of the financial performance of Microfinance Institutions (MFIs) in emerging and developing countries, focusing on the impact of foreign exchange risk and country-specific factors on their return on assets (ROA). The study examines the role of foreign exchange risk-related variables, MFI-specific characteristics, and macroeconomic factors. The study sample consists of data for 154 MFIs of 47 emerging and developing countries over the period 2018-2022. The data was collected from the Orbis, Passport databases, and the International Monetary Fund (IMF). The study examines the impact of foreign exchange risk, country-specific factors, and MFI characteristics on the performance of Microfinance Institutions using ordinary least squares, fixed effects, random effects, between models, and robust regression methods. We also estimate and compare the results for two subsamples of MFIs in hard/peg exchange rate regimes and floating-rate regimes. We find that MFIs operating in countries with higher interest rate differentials have lower ROA. Moreover, the ratios of Loans to Total assets, Interest Income over Loans, Impaired and Non-performing Loans over Loans, as well as GDP Growth and Rule of Law significantly influence MFI's financial performance. The results suggest that MFIs operating in pegged exchange rate regimes seem to have a higher sensitivity to (unexpected) exchange rate changes. The results underline the importance of effective risk management strategies.